Modification of Electrode Using Arrowroot Starch Membrane for Uric Acid Determination - Elvian Eka Krisnaniningrum; Ani Mulyasuryani; Hermin Sulistyarti (Molekul, 2021)
Arrowroot starch membrane-modified glassy carbon electrode were constructed for the determination of uric acid. The membrane consist of arrowroot starch, polyvinyl alcohol, uric acid, and crosslinker. The crosslinker used was sodium tripolyphosphate, citric acid, and glutaraldehyde. Carbon material was added to increase the sensitivity. The composition of membrane influences the electrodes sensitivity. The best composition of arrowroot starch membrane is UA1 using 0.1% uric acid in membrane and STPP as crosslinker. The linearity concentration, sensitivity, and detection limit were 100-500 µM, 0.0509 A/M and 76 µM, respectively.